New molecular evidence supports the species status of Kaempfer's Woodpecker (Aves, Picidae) - AZEVEDO, Lorena de Sousa (2013)
Kaempfer's Woodpecker (Celeus obrieni) is the only species of the genus Celeus endemic to Brazil. The description of this taxon as a subspecies of the Rufous-headed Woodpecker (Celeus spectabilis) was based on a single specimen. While C. obrieni and C. spectabilis are now considered separate species based on morphological and limited molecular evidence, no study has critically tested the reciprocal monophyly and degree of evolutionary independence between these taxa with several specimens. Herein, fragments of the mitochondrial and nuclear DNA of three recently-collected specimens of C. obrieni were analyzed to evaluate the degree of evolutionary differentiation of this taxon with respect to C. spectabilis. The results confirm the reciprocal monophyly between the specimens of C. obrieni and C. spectabilis. The genetic divergence values for the two taxa also support their classification as independent species, given that they are greater than the values recorded among other closely-related but separate species of the same genus. Estimates of the divergence time between C. obrieni and C. spectabilis indicate that cladogenesis occurred in the mid-Pleistocene, during a period of major climatic fluctuations and landscape change, consistent with the hypothesis of a corridor of open bamboo dominated forests and woodland stretching.